Altitude training for elite endurance performance: A 2012 update - Fudge, B. W.; Pringle, J. S. M.; Maxwell, N. S.; Turner, G.; Ingham, S. A.; Jones, A. M. (Current Sports Medicine Reports, 2012)
Altitude training is commonly used by endurance athletes and coachesin pursuit of enhancement of performance on return to sea level. The purpose of the current review article was to update and evaluate recentliterature relevant to the practical application of altitude training for endurance athletes. Consequently, the literature can be considered in eitherof two categories: performance-led investigations or mechanistic advance-ments/insights. Each section discusses therelevantliterature and proposesfuture directions where appropriate